Suffering, authenticity, and meaning in life: Toward an integrated conceptualization of well-being - Kaftanski, Wojciech; Hanson, Jeffrey (Frontiers in Psychology, 2022)
Most conceptions of well-being either ignore suffering or assume an ideal version of human life in which suffering would be eliminated. This trend is especially emblematic of positive psychology. Recent research on well-being indicates a mediating function of meaning in life between suffering and well-being demonstrating that making sense of past experiences is significantly correlated with high presence of meaning in life. Hence, meaning-making serves the role of an active coping mechanism that alleviates suffering. This and related strategies of defining, measuring, and augmenting well-being however overlook a form of suffering that is ineliminable and in fact essential to personal growth. In this paper the insights of the existentialist philosopher Søren Kierkegaard are developed to formulate an integrated conceptualization of well-being that regards “negative” affects as crucial for a rich and complete life. The complexity of the relationship between meaning in life, suffering, and authenticity concerning well-being are discussed. A synthetic perspective on the subjective dimension of the experience of suffering and on the objective nature of human limitations that often cause suffering is discussed in relation to the notions of meaning in life and authenticity. Finally, an integrated conceptualization of well-being is posited. It entails suffering as constitutive of meaning in life and authenticity, which are key components of a well-lived life.